A high-performance silicon/carbon composite as anode material for lithium ion batteries. (10th February 2021) - Bai, Yangzhi; Cao, Xinlong; Tian, Zhanyuan; Yang, Shifeng; Cao, Guolin
Abstract: To overcome the existing rapid capacity decay, low conductivity and the expands and contracts in volume of Si/C composite anodes in lithium ion batteries, we have developed a silicon/carbon composite by spray drying and twice organic carbon source cladding process. The samples are characterized by x-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectrometer, thermogravimetric analysis and x-ray photoelectron spectra (XPS). The electrochemical performance are analyzed by half-cell and full-cell experiments. The results show that the silicon/carbon composite is core–shell structure with the silicon embedded graphite as core and organic carbon layers as the shell, the particle size range from 8 μ m to 24 μ m. The first reversible capacity and initial coulombic efficiency of the silicon/carbon composite are 936.4 mAh g −1 and 88.6% in half-cell. The silicon/carbon composite exhibits a high capacity retention up to 80% after 680 cycles in full-cell, indicating an excellent cycling stability. The structure is beneficial to control volume expansion, improve conductivity and electrochemical performance.